Molecular detection of Ehrlichia Sp. in bat-associated chigger mites (trombidiformes: leeuwenhoekiidae and trombiculidae S. s.) from Brazil - Bassini-Silva, Ricardo; Mello-Oliveira, Victor de Souza [UNESP]; de Almeida, Beatriz Rocha [UNESP]; Pesenato, Isabella Pereira; Calchi, Ana Cláudia [UNESP]; Castro-Santiago, Ana Carolina; Lourenço, Elizabete Captivo; Famadas, Katia Maria; Welbourn, Cal; Ochoa, Ronald; André, Marcos Rogério [UNESP]; Labruna, Marcelo Bahia; et al. (Springer Nature, 2025)
Chigger mite larvae are well adapted parasites, mainly of vertebrates, and can play a role as potential vectors for pathogens, as is the case of the bacteria Orientia tsutsugamushi. In Brazil, 63 species of chiggers have been cataloged, eight of which were found parasitizing bats. Until now, no studies have monitored pathogens of bat-associated chigger species in the Americas. Here, we provide information about the detection of Ehrlichia sp. (16S rRNA gene) in Perissopalla ipeani Brennan larvae collected parasitizing the bat species Carollia perspicillata in Brazil.